Which Performance Measures Do Investors Around the World Value the Most—and Why? - Barton, Jan; Hansen, Thomas Bowe; Pownall, Grace (The Accounting Review, 2010)
ABSTRACT: We examine the value relevance of a comprehensive set of summary performance measures including sales, earnings, comprehensive income, and operating cash flows. We find that, while value relevance peaks for measures “above the line,” no single measure dominates around the world. Instead, a measure is more relevant when it captures, directly and quickly, information about firms’ cash flows. Specifically, for each performance measure by country, we estimate eight attributes commonly used to assess earnings quality. We find these attributes highly correlated—most of their variance is explained by only two principal factors. A factor capturing articulation with cash flows is positively associated with a measure’s value relevance; a factor reflecting the measure’s persistence, predictability, smoothness, and conservatism is negatively associated. Our results suggest that, when it comes to equity valuation, accounting researchers and standard-setters should focus not on what performance measure is “best” at a given point in time, but on the underlying attributes that investors find most relevant.